Pregled medicinsko-tehničnih pripomočkov pri osebah po amputacijah spodnjih udov - Rupnik Mihelčič, Sara (Rehabilitacija (Ljubljana), 2019)
Introduction: Amputation in older patients with several chronic diseases can cause great changes in their functional ability, which affects their independence in everyday tasks and participation. These issues can be reduced with suitable adaptations of the environment and medical aids. The aim of the article was to review which medical aids that are financed by the Health Insurance Institute of Slovenia are most frequently assessed for and prescribed to patients with lower limb amputation. Methods: The occupational therapists' documentation at the University Rehabilitation Institute in Ljubljana, where all medical aids being assessed and prescribed are recorded, was reviewed for rehabilitation patients after lower limb amputation. The timeframe was set between June and December 2017. Results: Medical documentation of 160 patients was reviewed (77.5% were men). One-hundred-and-fourteen patients (71.2%) received 185 items of medical aids. The patients received between 0 (46 patients, 28.8%) and 5 (1 patient, 0.6%) medical aids. The most frequently prescribed item was antidecubitus cushions, followed by shower stool/bath board and raised toilet seat. Conclusions: Lower limb amputees req
Keywords: amputacija; Amputation; delovna terapija; lower limb; medical aids; medicinsko tehnični pripomočki; Occupational Therapy; rehabilitacija; rehabilitation; spodnji ud; vocational rehabilitation